Emerging insights into the ependymoma epigenome - Mack, Stephen C.; Witt, Hendrik; Wang, Xin; Milde, Till; Yao, Yuan; Bertrand, Kelsey C.; Korshunov, Andrey; Pfister, Stefan; Taylor, Michael D. (Brain pathology, 2013)
Ependymoma is the third most common pediatric brain tumor, yet because of the paucity of effective therapeutic interventions, 45% of patients remain incurable. Recent transcriptional and copy number profiling of the disease has identified few driver genes and in fact points to a balanced genomic profile. Candidate gene approaches looking at hypermethylated promoters and genome-wide epigenetic arrays suggest that DNA methylation may be critical to ependymoma pathogenesis. This review attempts to highlight existing and emerging evidence implicating the ependymoma epigenome as a key player and that epigenetic modifiers may offer new targeted therapeutic avenues for patients.